The The perceptual mediated learning program for the blind children (Studia Doctoralia Psychology and Educational Science, 2012)
Tactile exploration is very important for the blind children and the development of the tactile sensitivity must begin from preschool period and must be realized step by step during a long period of time. As a therapist I was interested in training and developing the tactile perception regarding spatial relations in blind children. As a result I created The Perceptual Mediated Leaming Program in order to stimulate tactile sensitivity from preschool to the fourth grade. The Mediated Leaming Experience (MLE) was introduced by the theory's author of the cognitive structural modifiability, Reuven Feuerstein. This concept (MLE) underlies my program. The Perceptual Mediated Learning Program uses the dots and lines and their combinations and consists of the different sections: the dot, the group of the 6 dots, the line, the angle, the shapes, the draws with lines and shapes. Tactile exercises are graduated as difficulty. The program allows to find out how important the early education and preschool stimulation are for the development of the tactile sensitivity in blind children and their preparation for school, for Braille reading and writing.